Intraoperative radiotherapy (IORT) of early breast cancer with low-energy x-rays in breast-conserving surgery - Grimm, Anja; Wollmann, Eva Viola Christine; Sperk, Elena; Weiß, Christel; Sütterlin, Marc; Berlit, Sebastian; Tuschy, Benjamin (Strahlentherapie und Onkologie, 2023)
Purpose: The aim of this study is to identify pre- and intraoperative factors indicating the feasibility of intraoperative radiotherapy (IORT) during breast-conserving surgery (BCS). Materials and methods: From January 2018 to December 2019, a total of 128 women undergoing BCS due to early breast cancer were included in this prospective observational study, independent of whether IORT was planned or not. Patient and tumor characteristics as well as surgical parameters that could potentially influence the feasibility of IORT were recorded for the entire collective. In addition, a preoperative senological assessment was performed and analyzed to assess the feasibility of IORT. Logistic regression was then used to identify relevant preoperative parameters and to generate a formula predicting the feasibility of IORT. Results: Of the 128 included women undergoing BCS, 46 were preoperatively rated to be feasible, 20 to be questionably feasible for IORT. Ultimately, IORT was realized in 30 patients. The most frequent reasons for omission of IORT were insufficient tumor-to-skin distance and/or an excessively large tumor cavity. Small clinical tumor size and large tumor-to-skin distance according to preoperative ultrasound were significantly related to accomplishment of IORT. Conclusion: We observed that preoperative ultrasound-based tumor–skin distance is a significant factor in addition to already known parameters to predict feasibility of IORT. Based on our findings we developed a formula to optimize IORT planning which might serve as an additional tool to improve patient selection for IORT in early breast cancer.
Veröffentlicht: 04. Oktober 2023
Gesehen am 20.11.2023